Determinants of Child Care Participation - Katja Coneus; Kathrin Göggel; Grit Muehler (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
When estimating the determinants of child care participation, the simultaneity in mothers' decision to work and in the decision to use child care is a major challenge. In this study, we provide evidence on the determinants of institutional child care use accounting for the endogeneity of mothers' labor supply by applying an instrumental variables approach. This endogeneity has been neglected in studies on this issue so far, even though the decision to use child care outside the home is strongly connected to mothers' decision to work after childbirth and vice versa. Based on the German Socio-economic Panel (GSOEP) from 1989-2006 we show that children living in Western Germany have a higher probability to attend institutional care if their mothers increase their actual weekly working time. Estimating the determining factors of child care participation without correcting for simultaneity underestimates the influence of maternal working time by more than a half.
Keywords: 330